2014
DOI: 10.1007/s15010-014-0648-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological features of HIV/AIDS infection among migrants at first access to healthcare services as compared to Italian patients in Italy: a retrospective multicentre study, 2000–2010

Abstract: Late presentation still represents a relevant problem despite the advances in the management of HIV infection. More efforts are needed to allow early diagnosis and access to care among the most vulnerable, such as undocumented foreign-born subjects in a country where migration flows are on the rise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Indeed, patients presenting late were mostly males, migrants and older than individuals who presented earlier. Only in specific contexts female patients accounted for the majority of late presentations, especially because of the female component of the migrant population coming from Sub Saharian Africa [3032]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients presenting late were mostly males, migrants and older than individuals who presented earlier. Only in specific contexts female patients accounted for the majority of late presentations, especially because of the female component of the migrant population coming from Sub Saharian Africa [3032]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, immigrant patients represent a more vulnerable population: it has been already demonstrated that immigrants are more likely to have a delayed in access to HIV care and with concurrent advanced AIDS. 34 , 35 Furthermore in HIV-infected immigrants, the rate of retention to care is lower 36 and the rate of adherence to cART. 37 For these reasons, Italian physicians might have used different patterns of prescription for this population (eg, using regimens with high barrier to resistance) and subsequently immigrants have reduced possibility to discuss treatment simplifications with their treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Considering many undocumented migrants who were referred to the program had extremely low CD4 levels (Table 3), HIV care was essential to undocumented migrants in terms of improving quality of life for PLWHIV and preventing its spread in tight-knit communities. Such a situation is not unique to Israel; other researchers also described the high rate of delayed diagnosis among undocumented migrants in high income countries, with a significant percentage of AIDS-defining diseases at first presentation [29, 30]. While the program is limited to HIV care, it allows otherwise uninsured migrants some access to health services.…”
Section: Resultsmentioning
confidence: 99%